Political Islam in the Old and New Orders: Actions and Reactions of Islamic Figures Versus the State (1945-1973) - Imam Ibnu Hajar; M. Yunus Abu Bakar; Mochammad Nginwanun Likullil Mahamid (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This article examines the political landscape during Soekarno's rule (referred to as the Old Order/Orde Lama) and the early years of Soeharto's regime (New Order/Orde Baru). For Islamic political activists, the period from 1945 to 1973 was particularly challenging. Both the Old and New Orders governments were wary of Islamic parties, often blacklisting and marginalizing them. Employing historical research methods, including source collection (heuristic), source criticism, interpretation, and historiography, this article is a type of qualitative research conducted through literature study. The sources used include books from various libraries and the author's personal collection, as well as journal articles and proceedings accessed online via Google Scholar. The study is further supported by theories and political approaches, this article explores the struggle of Islamic activists during the 1955 elections, which were the first in Indonesia's history. Despite their efforts, they faced defeat rather than success, particularly in their attempts to establish Islam as the state foundation. During the New Order, Islamic groups continued to struggle. The government's strict political stance viewed the continuous criticism from Islamic parties as rebellious, leading to further suppression and their restriction to a single party, the United Development Party (Partai Persatuan Pembangunan/PPP). Additionally, this article highlights the challenges faced by Islamic activists in advocating for political participation under the pressure of an authoritarian regime. Artikel ini mengkaji lanskap politik selama masa pemerintahan Soekarno (dikenal sebagai Orde Lama) dan tahun-tahun awal rezim Soeharto (Orde Baru). Bagi aktivis politik Islam, periode dari tahun 1945 hingga 1973 sangat menantang. Baik pemerintahan Orde Lama maupun Orde Baru berhati-hati terhadap partai-partai Islam, seringkali memasukkan mereka ke daftar hitam dan meminggirkan mereka. Dengan menggunakan metode penelitian sejarah yang terdiri atas heuristik (pengumpulan sumber), kritik sumber, interpretasi, dan historiografi, artikel ini merupakan jenis penelitian kualitatif melalui studi pustaka, sumber yang digunakan adalah buku-buku dari berbagai perpustakaan maupun milik penulis pribadi, serta artikel jurnal dan prosiding yang diakses secara online pada Google Scholar. Selanjutnya diperkuat teori dan pendekatan politik, artikel ini mengeksplorasi perjuangan para aktivis Islam selama pemilu 1955, yang merupakan pemilu pertama dalam sejarah Indonesia. Meskipun upaya mereka pada akhirnya harus menuai kekalahan ketimbang keberhasilan, terutama dalam upaya untuk menjadikan Islam sebagai dasar negara. Selama Orde Baru, kelompok-kelompok Islam terus berjuang. Sikap politik pemerintah yang ketat menganggap kritik berkelanjutan dari partai-partai Islam sebagai pemberontakan, yang menyebabkan penindasan lebih lanjut dan pembatasan mereka pada satu partai tunggal, yakni Partai Persatuan Pembangunan (PPP). Selain itu, artikel ini juga menyoroti tantangan yang dihadapi aktivis Islam dalam memperjuangkan partisipasi politik mereka di tengah tekanan rezim yang otoriter.